Efectos cardiovasculares del veneno de Bothrops asper en corazón de anfibios - Morales, Orlando (1976)
Lyophilized Bothrops asper venom was assayed on toad heart in situ and frog heart in vitro to study cardiac abnormalities in the frequency, inotropic effect and arrhythmia. Heated venom was also used to test the effect of lower toxic molecular weight components.With either crude or heated venom the cardiac frequency was decreased, with a marked negative inotropic effect in the toad heart, which showed in several cases 2: 1 heart block.